Correlations between hemoglobin, serum ferritin, and soluble transferrin receptor levels in children aged 6-59 months - Fajar Diah Tri Kusumastuti; Sutaryo Sutaryo; Sri Mulatsih (Indonesian Pediatric Society, 2014)
Background Early detection of iron deficiency is important in young children to prevent iron deficiency anemia, which may cause permanent neurocognitive development disorders. Hemoglobin level is an insensitive tool for detecting iron deficiency without anemia, while serum ferritin levels may be influenced by infection and inflammation. However, soluble transferrin receptor (sTfR) is a sensitive marker for detecting iron deficiency, yet not widely used in daily practice.Objective To assess for correlations between hemoglobin, serum ferritin, and soluble transferrin receptor levels in children aged 6-59 months.Methods We performed a cross-sectional study in the Yogyakarta and Bantul Districts involving 85 children aged 6-59 months who visited integrated health posts (posyandu) and who met the inclusion criteria. Subjects were chosen by cluster random sampling. Blood specimens were collected to examine hemoglobin, serum ferritin, and sTfR levels.Results Spearmanâ€™s correlation test revealed weak negative correlations between hemoglobin and serum ferritin levels, as well as between hemoglobin and sTfR levels, with coefficient correlations of r = -0.220, (P=0.043) and r = -0.317, (P=0.003), respectively. There was no correlation between serum ferritin and sTfR levels (r = -0.033; P=0.767).Conclusion Hemoglobin levels has weak negative correlations with serum ferritin and sTfR, but serum ferritin does not correlate with sTfR.Â [Paediatr Indones. 2014;54:122-6.]